ANALISIS BREAK EVEN POINT (BEP) DAN EFISIENSI USAHA PEMBIBITAN SAPI POTONG DI KOTA SAMARINDA - Candraputri Nugrahaeni; Kumbawan Wibisono (Jurnal Peternakan Lingkungan Tropis, 2019)
Husbandry and Animal Health Division of Samarinda Agriculture Departement make research was conducted to determine the Break Even Point (BEP) and business efficiency of cattle breeding farm in Samarinda. Research was done from July up to September 2018. The using method of survey to collect primary data at the respondent and secondary data from related institutions. The analysis showed that the Break Even Point price costs Rp. 19,105,978.32 with production volume BEP is 2, its means the business of cattle breeding benefit suffered if livestock raising cattle that are as much as two head and the business efficiency value is 1.33